THE EFFECTIVENESS OF MASSAGE THERAPY IN REDUCING PAIN IN POSTPARTUM MOTHERS: A LITERATURE REVIEW - Sukmawati, Sukmawati; Kosim, Kosim (Journal of Maternity Care and Reproductive Health, 2026)
Pain can be experienced by mothers during labor or after labor (postpartum), which can disrupt the mother's comfort and activities. This must be handled quickly and appropriately to prevent more serious complications, one of which is related to massage therapy. The purpose of this study was to determine the effectiveness of massage therapy in reducing pain in postpartum mothers. The research method used was a literature review, with articles searched through Scopus, PubMed, and Medline databases. The inclusion criteria were randomized controlled trials (RCTs), quasi-experimental studies (QE), experimental studies, and comparative studies, all of which used primary data, articles published between 2019 and 2024, study population of postpartum mothers, independent variable of massage therapy and dependent variables of pain in postpartum mothers, articles in Indonesian and English, accessible, and available in full text. The keywords used were "Postpartum" OR "Postpartum period" Massage therapy", "Nursing intervention", "Pain management". The quality of the studies was assessed using the Joanna Briggs Institute (JBI). From the results of the research selection of 55 articles, there were 10 articles that met the inclusion and eligibility criteria for analysis. All research results showed that massage therapy interventions can be used by postpartum mothers to reduce pain, namely Massage and Acupressure, Effleurage Massage, Effleurage Massage and Relaxation, Deep Tissue Massage, Hand and Foot Massage, Foot Massage, and Foot Reflexology. Based on the findings obtained, massage therapy interventions can reduce pain in postpartum. Massage therapy can be recommended as an intervention to reduce postpartum pain.